Performance evaluation of a new on-demand molecular test for the rapid identification of severe acute respiratory syndrome coronavirus 2 in pediatric and adult patients - Colagrossi, Luna; Costabile, Valentino; Scutari, Rossana; Cento, Valeria; Coltella, Luana; Reale, Antonino; Scilipoti, Martina; Villani, Alberto; Alteri, Claudia; Perno, Carlo Federico; Russo, Cristina (Frontiers in Microbiology, 2022)
The rapid spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has increased the need to identify additional rapid diagnostic tests for an accurate and early diagnosis of infection. Here, we evaluated the diagnostic performance of the cartridge-based reverse transcription polymerase chain reaction (RT-PCR) test STANDARD M10 SARS-CoV-2 (SD Biosensor Inc., Suwon, South Korea), targeting the ORF1ab and E gene of SARS-CoV-2, and which can process up to eight samples in parallel in 60 min. From January 2022 to March 2022, STANDARD™ M10 assay performance was compared with Xpert® Xpress SARS-CoV-2 (Cepheid, Sunnyvale CA) on 616 nasopharyngeal swabs from consecutive pediatric (N = 533) and adult (N = 83) patients presenting at the “Istituto di Ricovero e Cura a Carattere Scientifico” (IRCCS) Ospedale Pediatrico Bambino Gesù, Roma. The overall performance of STANDARD M10 SARS-CoV-2 was remarkably and consistently comparable to the Xpert® Xpress SARS-CoV-2 with an overall agreement of 98% (604/616 concordant results), and negligible differences in time-to-result (60 min vs. 50 min, respectively). When the Xpert® Xpress SARS-CoV-2 results were considered as the reference, STANDARD™ M10 SARS-CoV-2 had 96.5% sensitivity and 98.4% specificity. STANDARD M10 SARS-CoV-2 can thus be safely included in diagnostic pathways because it rapidly and accurately identifies SARS-CoV-2 present in nasopharyngeal swabs.